2012
DOI: 10.1111/j.1741-6787.2012.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Online Journal Club on Evidence‐Based Practice Knowledge, Intent, and Utilization in School Nurses

Abstract: A school nurse online journal club is one strategy to bring evidence to practitioners. Technology exists for nurses experiencing practice isolation to connect through online avenues. Nursing researchers, educators, and administrators seeking to disseminate research to school nurses or other clinical specialties could replicate or expand this project. Expanding online journal clubs would allow busy clinicians to connect with colleagues and researchers to integrate evidence into practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
0
33
0
3
Order By: Relevance
“…39 Athletic trainers who work alone or in physical isolation from others may lack relationships with other health care professionals who could assist them with implementing evidence into patient care and further their professional development. 40 To improve the possibility of implementing EBP, ATs are encouraged to look beyond the idea that they must interact professionally only with ATs and begin to build a community of other health care professionals in their area, such as a team physician, school nurse, or physical therapist. By collaborating with other health care providers, ATs can improve patient care, reduce some of the burden of understaffing, and advance their knowledge of current practices and evidence.…”
Section: Participants' Ebp Beliefsmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Athletic trainers who work alone or in physical isolation from others may lack relationships with other health care professionals who could assist them with implementing evidence into patient care and further their professional development. 40 To improve the possibility of implementing EBP, ATs are encouraged to look beyond the idea that they must interact professionally only with ATs and begin to build a community of other health care professionals in their area, such as a team physician, school nurse, or physical therapist. By collaborating with other health care providers, ATs can improve patient care, reduce some of the burden of understaffing, and advance their knowledge of current practices and evidence.…”
Section: Participants' Ebp Beliefsmentioning
confidence: 99%
“…School nurses who participated in the study reported feeling more connected with colleagues (82%), an increased comprehension of the evidence in the articles discussed (82%), and a better understanding of the link between evidence and practice. 40 Endslay et al 41 suggested forming a community of practice for those who share a common interest and seek to deepen their knowledge and expertise. Building a community through local or online resources will help ATs who work in isolated locations gain access to other health care professionals who ''share a concern, a set of problems, or a passion about a topic, and who deepen their knowledge and expertise in this area by interacting on an ongoing basis.''…”
Section: Participants' Ebp Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A review of the nursing literature supports the role of journal clubs in improving research awareness. 13,14,16,19 The role for journal clubs to potentially improve patient care through reviewing and discussing research articles with nursing peers as well as on their own is significant, as the amount of time nurses spend reading research articles has been correlated with adopting changes in practice to improve patient outcomes. 12,20 There's evidence that continued participation in a journal club increases the likelihood that members will read the proposed journal article.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They aid in teaching the systematic evaluation and interpretation of the published literature and are a means to share the latest advances in medicine. The journal club is approaching 200 years of age, however, it continues to evolve to solve new problems and employ new technologies [1][2][3] . The latest example of this is journal clubs using social media to discuss and debate the published literature.…”
Section: Introductionmentioning
confidence: 99%